Clinical Holistic Medicine: Teaching Orgasm for Females with Chronic Anorgasmia using the Betty Dodson Method - Pia Struck; Søren Ventegodt (The Scientific World Journal)
The objective of this study was to test the Betty Dodson method of breaking the female orgasm barrier in chronic anorgasmic women. The aim was sexual and existential healing (salutogenesis) through direct confrontation and integration of both the repressed shame, guilt, and other negative feelings associated with body, genitals, and sexuality, and the repressed sexual pleasure and desire. We conducted a retrospective analysis of clinic data from holistic sexological manual therapeutic intervention, an intensive subtype of clinical holistic medicine (CHM). The patients received 3 × 5 h of group therapy, integrating short-term psychodynamic psychotherapy (STPP) and complementary medicine (CAM bodywork, manual sexology similar to the “sexological examination”). The therapy used the advanced tools of reparenting, genital acceptance, acceptance through touch, and direct sexual clitoral stimulation. A clitoral vibrator was used. Participants were 500 female patients between 18 and 88 years of age (mean of 35 years) with chronic anorgasmia (for 12 years on average) who were participating in the “orgasm course for anorgasmic women”; 25% of the patients had never experienced an orgasm. Our results show that 465 patients (93%) had an orgasm during therapy, witnessed by the therapist, and 35 patients (7%) did not. Postmenopausal women were as able to achieve orgasm as fertile women, as were women who never had an orgasm. No patients had detectable negative side effects or adverse effects. NNT: 1.04 < NNT < 1.12, NNH > 500. Therapeutic value: TV = NNH/NNT > 446. Our conclusions are that holistic sexological manual therapy may be rational, safe, ethical, and efficient.